2014
DOI: 10.1002/jcla.21728
|View full text |Cite
|
Sign up to set email alerts
|

Performances of Capillary Electrophoresis and HPLC Methods in HbA1c Determination: Diagnostic Accuracy in HbS and HbD‐Iran Variants' Presence

Abstract: Since the HbA1c test is now recommended for diagnosing diabetes, and minimal variation of the concentration affects the clinical therapy, it is very important that the results are reliable and interference-free. Capillarys 2-FP analyzer is suitable for this purpose and sometimes it showed some advantages with respect to the HPLC analyzers tested, especially when Hb variants are present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Recently, capillary 2-FP analyzer has been found to be suitable for HbA1c measurement, and sometimes, it showed some advantages with respect to the HPLC analyzers tested, especially when Hb variants are present. 72 …”
Section: Methods For Hba1c Analysismentioning
confidence: 99%
“…Recently, capillary 2-FP analyzer has been found to be suitable for HbA1c measurement, and sometimes, it showed some advantages with respect to the HPLC analyzers tested, especially when Hb variants are present. 72 …”
Section: Methods For Hba1c Analysismentioning
confidence: 99%
“…HbA 1c is used as the gold standard for monitoring long‐term glycemic control in people with diabetes mellitus and is characterized by nonenzymatic binding of glucose to the N‐terminal valine residue on the β‐chain of the HbA . Previously, studies have shown that hemoglobin variants can affect the detection of HbA 1c . In this study, we incidentally found a variant of the α2 chain in a Chinese individual following HbA 1c analysis.…”
Section: Introductionmentioning
confidence: 68%
“…C2FP is a new assay to evaluate HbA 1c based on the separation of Hb property and charge by capillary electrophoresis. There is a strong consistency between the results of C2FP and VII [19]. Many literatures have reported that the resolution of C2FP is superior to CE-HPLC resulting from allowing the separation of many common and rare Hb variants from the HbA0 fraction [19–21].…”
Section: Discussionmentioning
confidence: 88%